Communication Strategy Of The Head Of The Office Of Religious Affairs In Realizing The Five Work Culture Values In North Sumatra - Bangunan, Marasakti; Kholil, Syukur; sahrul, sahrul (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research uses qualitative in describing the data. The location or place of research is in North Sumatra. namely a province in Indonesia which is in the northern part of the island of Sumatra, bordering Aceh to the north, with West Sumatra and Riau to the south. There were 11 research informants. The way to get the data uses triangulation and data analytical methods consisting of three simultaneous operational flows: data reduction, data presentation, and conclusion drawing/verification. Communication planning is important to overcome various obstacles, to create effective and efficient communication, in realizing the five work culture values of the Ministry of Religion of the Republic of Indonesia. The results of the research provide an illustration that there are three aspects of communication planning carried out by the head of the KUA, 1) work communication planning, namely communication between employees which consists of downward communication, upward communication and horizontal communication, 2) service communication planning, namely communication carried out by the apparatus (head of KUA) in providing services to the community, either directly or through the media. 3) transformative communication planning, namely the process of conveying messages that requires the participation of all elements involved in the communication, such as communication carried out by the prospective bride and groom in order to take care of the completeness of the wedding administration according to the provisions.